Model Matematis Pengaruh Lembaga Pembiayaan Syariah dan Konvensional terhadap Pertumbuhan Ekonomi Indonesia - Nurjanah, Putri Leli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to analyze the influence of sharia insurance and sharia financing institutions on Indonesia's economic growth and to analyze the influence of conventional insurance data and conventional financing institutions both partially and simultaneously through empirical studies with a quantitative approach. Using an associative research method with a quantitative research approach. Multiple linear regression analysis OLS is used as a data analysis method. The data used comes from the official websites of OJK and BPS in the form of quarterly data for the period 2015-2022. The findings show that sharia and conventional insurance products and financing institutions each have an influence on Indonesia's economic growth. Insurance products and financing institutions are one type of investment. Where investment can increase economic growth because through investment it will increase production capacity. Sharia and conventional IKNB are a collection of financial institutions that are able to act as intermediaries for collecting and distributing capital so that they can help the economy and thereby increase Indonesia's economic growth. Conclusion, sharia and conventional insurance products and financing institutions play an important role in increasing Indonesia's economic growth, because both are forms of investment that can increase production capacity and help collect and distribute capital, which ultimately supports the running of the economy. Keywords: Sharia, Conventional IKNB, Indonesian Economic Growth